Which Degree for which Profession of Medicine in Spain? The Failure of the Introduction of Social Health Sciences in the Medical Education of the First Franco Regime (1938-1959) - Barceló-Prats, Josep; Comelles, Josep M. (Historia y Memoria de la Educación, 2021)
Beginning at the end of the 18th century, the emergence of hospital medicine and, half a century later, the development of experimental medicine and health statistics, transformed the way medicine was taught. This new training model prioritized the “clinical view”, to the detriment of the view on the social environment where professional practice was undertaken. Despite this subordination, on an international scale, social medicine and other social and health sciences continued to be important subjects in the medical curriculum. However, in Spain the presence of social and health sciences was scant. In this article, focused mainly on the early Franco regime, we intend to clarify the roots and reasons for this marginalization, such as the legal and administrative “regulations” of the Spanish university; academic and corporate resistance to incorporating interdisciplinary approaches; and a political and ideological context that delayed, until the Spanish Transition, the evolution of Spanish health towards the concept of “public health”. To do this, we have divided the article into two parts. The first follows the evolution of medical training from the middle of the 19th century to 1938, while the second describes and analyses the reforms of medical curricula made between 1938 and 1959.